2023
DOI: 10.1111/1471-0528.17668
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals in menstrual products: A systematic review

Joanna Marroquin,
Marianthi‐Anna Kiomourtzoglou,
Alexandra Scranton
et al.

Abstract: BackgroundFrom menarche until menopause, the average menstruator will use over 11 000 tampons or sanitary pads. Vaginal and vulvar tissue is highly permeable, and chemicals are absorbed without undergoing first‐pass metabolism.ObjectivesTo conduct a review of the literature to determine exposure to environmental chemicals in menstrual products.Search strategyThis review identified 15 papers over the past 10 years.Selection criteriaPapers that measured chemicals in menstrual products and that measured human bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Yet, PFAS is not the only chemical group of concern for human health. Humans are exposed to a plethora of chemical compounds on a regular basis, including industrial chemicals and chemicals found in building materials, household products, cosmetics and hygiene products, to name a few (Panico et al 2019;Rousseau et al 2022;Marroquin et al 2023). There consequently exists a need to understand, not only the potential effects of PFAS exposure on human health but also of possible combined effects that chemical mixtures may have on human health.…”
Section: General Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Yet, PFAS is not the only chemical group of concern for human health. Humans are exposed to a plethora of chemical compounds on a regular basis, including industrial chemicals and chemicals found in building materials, household products, cosmetics and hygiene products, to name a few (Panico et al 2019;Rousseau et al 2022;Marroquin et al 2023). There consequently exists a need to understand, not only the potential effects of PFAS exposure on human health but also of possible combined effects that chemical mixtures may have on human health.…”
Section: General Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition, despite the above findings, it may still be difficult to disentangle the evolutionary issues from other epidemiological aspects ( Eaton et al , 2002 ), and since retrograde menstruation is reported to be a common phenomenon in most menstruators ( Halme et al , 1984 ; Liu and Hitchcock, 1986 ; Tang et al , 2022 ), multiple factors in addition to ROM are likely to play a role in the development of endometriosis and adenomyosis ( Shafrir et al , 2018 ; Zondervan et al , 2018 , 2020 ; Koninckx et al , 2019 ; Leonardi et al , 2020 ; Olšarová and Mishra, 2020 ; WaNg et al , 2020 ; Kuan et al , 2021 ; Salliss et al, 2021 ; Taylor et al , 2021 ; Horne and Missmer, 2022 ; Marroquin et al , 2023 ; Muraoka et al , 2023 ; Vallée et al , 2023 ; Yang et al , 2023 ). Even an increase in endocrine-disrupting chemicals due to air and water pollution and occupational hazards can potentially lead to the onset and progression of endometriosis ( Vallée et al , 2023 ).…”
Section: What Does Social Evolution Have To Do With Endometriosis And...mentioning
confidence: 99%
“…(ii) Second, in addition to repetitious ovulatory cycles, several other factors appear to play a role in the pathogenesis of endometriosis and adenomyosis, including genetic predisposition, epigenetic profile, constitutional variables, immunological and hormonal factors, and individual lifestyle ( Shafrir et al , 2018 ; Zondervan et al , 2018 , 2020 ; Bulun et al , 2019 , 2021 , 2023 ; Guo, 2020 , 2023 ; WaNg et al , 2020 ; Taylor et al , 2021 ; Horne and Missmer, 2022 ; Vallée et al , 2023 ). Thus, even if there is an actual progressive increase in frequency, this could be explained by augmented exposure to toxic environmental chemicals and endocrine disruptors ( Sirohi et al , 2021 ; Matta et al , 2021 ; Vallée et al , 2023 ; Marroquin et al , 2023 ), high trans-unsaturated fat intake ( Missmer et al , 2010 ), altered microbiome ( Koninckx et al , 2019 ; Leonardi et al , 2020 ; Salliss et al, 2021 ; Muraoka et al , 2023 ; Yang et al , 2023 ), or other features of modern life that may influence the risk of these diseases ( Missmer and Cramer, 2003 ; Viganò et al , 2004 ; Ottolina et al , 2020 ; Sasamoto et al , 2020 ; Shafrir et al , 2018; Koninckx et al , 2021a ). More in general, since endometriosis and adenomyosis appear as multistep phenomena in which, after an establishment phase, a proliferation and invasion phase occurs, accompanied or followed by an inflammatory reaction phase, each phase may be subject to the influence of different contributing factors ( Parazzini et al , 2017 ).…”
Section: Criticisms Of the Repetitive Ovulatory Menstruation Hypothesismentioning
confidence: 99%
See 2 more Smart Citations